Point-contact-spectroscopy evidence of quasi-particle interactions in RNi₂B₂C(R=Ho, Y) - Jansen, A.G.M.; Wyder, P.; Yanson, I.K.; Fisun, V.V.; Canfield, P.C.; Cho, B.K.; Tomy, C.V.; McK. Paul, D. (Физика низких температур, 1997)
The point-contact (PC) d²V/dI²-spectra of HoNi₂B₂C and YNi₂B₂C reveal structure at applied voltages corresponding to the phonon frequencies. At about 4 meV a maximum is observed in the phonon density of states by analogy to the soft-phonon structure in neutron scattering experiments for LuNi₂B₂C [ P. Dervenagas et al., Phys. Rev. B52, R9839 (1995)] and YNi₂B₂C [H. Kawano et al., Cech. J. Phys. 46, S2-825 (1996) Phys. Rev Lett. 77, 4628 (1996)]. In the Ho compound the low-energy phonon peak is suppressed by an applied magnetic field in an anisotropic way, pointing to an interaction between the phonons and the magnetic systems Surprisingly, in the nonmagnetic Y compound the 4-meV peak is also suppressed by a magnetic field. In the Ho-compound contacts which show the «quasi-thermal» behavior, the detailed magnetic-field and temperature dependences of the PC spectra suggest that the magnetic order is destroyed due to the coupled phonon-magnon subsystem which is driven out of equilibrium by electrons that pass through the contact, by analogy with the nonequilibrium phonon-induced destruction of the superconducting state in point contacts [I. K. Yanson et al., JETP Lett 45, 543 (1987)]. The PC electron-phonon interaction (EPI) spectral functions are reconstructed and the estimates for the λ-parameter yield values of the order of 0.1. Comparison with PC EPI spectra of nonsuperconducting and nonmagnetic LaNi₂B₂C [I K. Yanson et al, Phys Rev. Lett. 78, 935 (1997)], as well as the comparative study of PC EPI and Andreev-retlection spectra tor various contacts with superconducting Ho and Y compounds suggest that the low-energy part ot the electron-quasi-particle interaction spectral function is responsible for the Cooper pairing in these materials.